2015
DOI: 10.1099/mic.0.000070
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of aflatoxin production by Aspergillus flavus and Aspergillus parasiticus in interaction with Streptomyces

Abstract: The aim of this study is to investigate aflatoxin gene expression during Streptomyces-Aspergillus interaction. Aflatoxins are carcinogenic compounds produced mainly by Aspergillus flavus and Aspergillus parasiticus. A previous study has shown that Streptomyces-A. flavus interaction can reduce aflatoxin content in vitro. Here, we first validated this same effect in the interaction with A. parasiticus. Moreover, we showed that growth reduction and aflatoxin content were correlated in A. parasiticus but not in A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…In fact, in our experiments, we did not observe any statistically significant change in A. flavus biomass during co-culture with L. monocytogenes (data not shown). This observation is in accordance with Verheecke et al [48], reporting that growth was not correlated with AFB1 in A. flavus during co-culture conditions. Furthermore, in the present study, the influence of this co-existence in A. flavus relative gene expression was also assessed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, in our experiments, we did not observe any statistically significant change in A. flavus biomass during co-culture with L. monocytogenes (data not shown). This observation is in accordance with Verheecke et al [48], reporting that growth was not correlated with AFB1 in A. flavus during co-culture conditions. Furthermore, in the present study, the influence of this co-existence in A. flavus relative gene expression was also assessed.…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, the downregulation of aflM and aflP during monoculture, as well as aflM and aflS during co-culture, were observed. These results are also in concordance with Verheecke et al [48] who similarly observed that the expression of aflM was repressed by Streptomyces presence and was also correlated with AFB1 content. The complex influence that temperature may have on the regulation of A. flavus aflatoxin biosynthetic pathway has been previously demonstrated [14,53].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Quantitative real-time PCR (qPCR) was carried out in triplicate in a LightCycler 96 instrument (Roche, Germany) using 100 ng cDNA, 0.5 µM each primer (Table S1) and qPCR BIO SyGreen Mix Lo-ROX (PCR Biosystem, UK) in 10 µl of total volume. The act1 gene (ACLA_095800) was used as reference gene (Bohle et al, 2007;Verheecke et al, 2015). Threshold cycle (C t ) determination was performed using LightCycler 96 software (Roche, Germany).…”
Section: Rna Purification Cdna Synthesis and Qpcrmentioning
confidence: 99%
“…However, to better understand how microbe-related inhibition of aflatoxin occurs, the aflatoxin-biosynthetic processes and the related genes will be discussed. To this end, there are interesting studies on the possible mechanisms responsible for the down-regulation of the transcription-activator genes aflS (formerly aflJ ) and aflR [ 75 103 ] in Aspergillus spp. Changes in the aflR / aflS -expression ratio in response to temperature and water activity have also been reported [ 102 ].…”
Section: Control Of Fungal and Mycotoxin Contamination In Stored Ricementioning
confidence: 99%